GluDB: A glaucoma associated gene database. (2019) - Duraisamy, Anitha; Suganthi, M.; Shanmugam, Gnanendra; Suryadevara, Nagaraja
Abstract: Glaucoma is the second leading cause of blindness across the globe and is estimated with a rise in prevalence in 79.6 million people by the year 2020. Glaucoma, as a most complex disease it is categorized into primary and secondary. The pathogenesis is attributed with multiple molecular mechanisms underlying the association of multiple genes with varying magnitudes of effects. The hallmark genes of glaucoma being myocilin (MYOC), optineurin (OPTN) and neurotrophin-4 (NTF4) in primary open-angle glaucoma (POAG) are already well associated with glaucoma. However, the candidate genes that are associated with glaucoma at various stages of pathogenesis and their genetic heterogeneity could significantly be emphasized as a novel therapeutic target of glaucoma. In line with this, we provide GluDB (http://glaucomahq.info ) as repository of the genes and candidate genes associated with glaucoma and also their association with various diseases. The GluDB holding nearly 700 genes associated with glaucoma would serves as ecstasy resource for the eye researcher and can be a source for the development of novel therapeutics against glaucoma.